Kesenian Sintren dalam Tarikan Tradisi dan Modernitas - Puji Dwi Darmoko (Sekolah Tinggi Ilmu Tarbiyah (STIT) Pemalang, 2014)
In the midst of the pressure of modernity, cultural products as a valuable culture created by the children of the nation are maintained. One of them is the regional art